Pengembangan Buku Sejarah Kebudayaan Islam Kelas VIII Berbasis Higher Order Thinking Skills - Purwaningrum, Septiana; Wati, Dewi Trisna (Edudeena : Journal of Islamic Religious Education, 2023)
Abstract: This research and development aims to 1) find out the needs in learning Islamic Cultural History (SKI) in class VIII; 2) planning the development of a HOTS-based SKI book; 3) knowing the validity of the SKI book development; 4) determine the level of effectiveness of SKI books. This study uses a sequential mixed method approach using the ADDIE model. Data collection techniques used validation questionnaires, response questionnaires, interviews, observations, and documentation conducted at Madrasah Tsanawiyah (MTs) Negeri 1 Kediri City. The results of research and development show that problems in learning SKI are that SKI books are not complete and are still conventional; no interactive ski books; SKI teachers do not bring up HOTS-oriented SKI learning. Second, the design produced is in the form of a color printed SKI book media equipped with HOTS-based questions, as well as a QR code. Third, the average result of the assessment of material experts, linguists, media experts, and student responses is 3.73. It can be said that the validity level of the HOTS-based SKI book is very high. Fourth, the effectiveness of learning using the HOTS-based SKI book obtained a significant increase in 32 students with an average score of 76 points on the pre-test and 90 on the post-test so that product development can be said to be effective for use in SKI learning. Abstrak: Penelitian dan pengembangan ini bertujuan untuk 1) mengetahui kebutuhan dalam pembelajaran Sejarah Kebudayaan Islam (SKI) pada kelas VIII; 2) membuat perencanaan pengembangan buku SKI berbasis HOTS; 3) mengetahui validitas pengembangan buku SKI; 4) mengetahui tingkat keefektifan buku SKI. Penelitian ini menggunakan pendekatan sequential mixed method dengan menggunakan model ADDIE. Teknik pengumpulan data menggunakan angket validasi, angket respon, wawancara, observasi, dan dokumentasi yang dilakukan di Madrasah Tsanawiyah (MTs) Negeri 1 Kota Kediri. Hasil penelitian dan pengembangan menunjukkan masalah dalam pembelajaran SKI adalah buku SKI belum lengkap dan masih konvensional; tidak adanya buku SKI yang interaktif; guru SKI kurang memunculkan pembelajaran SKI yang beriorientasi pada HOTS. Kedua, desain yang dihasilkan berupa media buku cetak SKI yang berwarna dilengkapi dengan soal-soal berbasis HOTS, serta terdapat kode QR. Ketiga, hasil rata-rata penilaian dari ahli materi, ahli bahasa, ahli media, dan respon siswa sebesar 3,73. Dapat dikatakan tingkat kevalidan buku SKI berbasis HOTS sangat tinggi. Keempat, keefektifan pembelajaran dengan menggunakan buku SKI berbasis HOTS diperoleh peningkatan yang signifikan terhadap 32 siswa dengan rerata skor 76 poin pada pre-test dan 90 pada post-test sehingga produk pengembangan dapat dikatakan efektif untuk digunakan dalam pembelajaran SKI.